How physics confronts reality : Einstein was correct, but Bohr won the game - Newton, Roger G. (World Scientific, 2009)
"This book recalls, for nonscientific readers, the history of quantum mechanics, the main points of its interpretation, and Einstein's objections to it, together with the responses engendered by his arguments. We point out that most popular discussions on the strange aspects of quantum mechanics ignore the fundamental fact that Einstein was correct in his insistence that the theory does not directly describe reality. While that fact does not remove these counterintuitive features, it casts them in a different light."--page vi.